الرجال الذين اخرج لهم الشيخان و ضعفهم ابو العرب الافريقي - مشري, عثمان; دردوري, البشير (University of eloued جامعة الوادي, 2021)
"ملخص البحث تطرقنا في هذا البحث الى الامام ابي العرب الافريقي من رجال الشيخين وكان ذلك في خطة بحث متكونة من مقدمة وفصلين وخاتمة... وقد تطرقنا فقي الفصل الأول الى التعريف الموسع لابي العرب والفصل الثاني ذكرنا فيه مبحثين حيث المبحث الأول خاص بأكابر اتباع التابعين والمبحث الثاني بأصاغر التابعين الذين ضاعفهم أبو العرب وكان من نتائج البحث ان الشيخان يرويان للرواة انتقاءا وأكثر من ضعفوا لم يثبت فيهم التضعيف وان أكثر كلام ابي العرب كان في الكوفيين نظرا لكثرة التشيع فيهم وان العبرة عند الشيخين بصدق اللهجة من رمي بالبدعة. "Research Summary In this research, we touched upon Imam Abu Al-Arab Al-Afriqi from the men of the two sheikhs, and that was in a research plan consisting of an introduction, two chapters and a conclusion... In the first chapter we touched on the expanded definition of Abu Al-Arab, and in the second chapter we mentioned two chapters in it, where the first topic concerns the most senior followers of the followers and the second topic deals with the youngest followers who were doubled by Abu Al-Arab. The Arabs were in the Kufics due to the large number of Shiites in them. And the lesson for the two sheikhs is the sincerity of the tone from the accusation of heresy
Keywords: " : أبو العرب – التخريج للضعفاء – منهج الشيخين – كيفية اخراج الشيخين "; Abu al-Arab - The graduation of the weak - the approach of the two sheikhs - how to extract